Sex differences in sequelae from COVID-19 infection and in long COVID syndrome: a review. (3rd August 2022) - Sylvester, Shirley V.; Rusu, Rada; Chan, Biankha; Bellows, Martha; O'Keefe, Carly; Nicholson, Susan
Abstract: Objective: We conducted literature reviews to uncover differential effects of sex on sequelae from coronavirus disease 2019 (COVID-19) and on long COVID syndrome. Methods: Two authors independently searched OvidSP in Embase, Medline, Biosis, and Derwent Drug File. Publications reporting original, sex-disaggregated data for sequelae of COVID-19 (published before August 2020) and long COVID syndrome (published before June 2021) were included in the reviews. The association between COVID-19 sequelae (i.e. lasting <4 weeks after symptom onset) and sex, and between long COVID syndrome (i.e. lasting >4 weeks after symptom onset) and sex, was determined by odds ratio (OR) and 95% confidence interval (CI) (statistical significance defined by 95% CI not including 1). Results: Of 4346 publications identified, 23 and 12 met eligibility criteria for COVID-19 sequelae and long COVID syndrome, respectively. COVID-19 sequelae in the categories of psychiatric/mood (OR = 1.80; 95% CI: 1.35–2.41), ENT (OR = 1.42; 95% CI: 1.39–1.46), musculoskeletal (OR = 1.15; 95% CI: 1.14–1.16), and respiratory (OR = 1.09; 95% CI: 1.08–1.11) were significantly more likely among females (vs. males), whereas renal sequelae (OR = 0.83; 95% CI: 0.75–0.93) were significantly more likely among males. The likelihood of having long COVID syndrome was significantly greater among females (OR = 1.22; 95% CI: 1.13–1.32), with the odds of ENT (OR = 2.28; 95% CI: 1.94–2.67), GI (OR = 1.60; 95% CI: 1.04–2.44), psychiatric/mood (OR = 1.58; 95% CI: 1.37–1.82), neurological (OR = 1.30; 95% CI: 1.03–1.63), dermatological (OR = 1.29; 95% CI: 1.05–1.58), and other (OR = 1.36; 95% CI: 1.25–1.49) disorders significantly higher among females and the odds of endocrine (OR = 0.75; 95% CI: 0.69–0.81) and renal disorders (OR = 0.74; 95% CI: 0.64–0.86) significantly higher among males. Conclusions: Sex-disaggregated differences for COVID-19 sequelae and long COVID syndrome were observed. Few COVID-19 studies report sex-disaggregated data, underscoring the need for further sex-based research/reporting of COVID-19 disease.